Flexibility as a Tool to Improve Functionality and Comfort Level of the Five Star Hotel Standard Rooms, A Case Study of the Hotels at South-East Coast of North Cyprus - Omar, Qusai Majed Harbi Abu (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
One of the most significant processes in interior architecture is flexibility, which refers to the possible adjustment to the requirements of all alternative situations and patterns of interior architecture in a dynamic system, or the creation of the designed geometric shape that is more connected and meets the requirements of the intended function. In addition, the flexible solutions can help in the creation of changeable space and help in the division of the space for the required functions to meet the user needs. The main aim for this thesis is to give a comprehensive idea about flexibility as a tool to improve functionality and comfort level of the five star hotel standard rooms by applying the flexible solutions processes to establish a changeable space, which is applied on the hotel rooms in order to increase the number of users and functions. To achieve that aim, first the flexible solutions will be derived from existing industries and researches like articles and multiple theses, which were completed already. Then the hotel rules and regulations of TRNC will be studied, where the case study in the thesis will be about the five-star hotels in South-East Coast of North Cyprus cities. As well, the classifications of TRNC will be studied as the main base for the design and the analysis of the case studies. After that, the application of the flexible solutions on the hotel room is to be looked into prove the potential for flexibility to meet the user's requirements and their changing needs of space. In general, this study is intended to help the five-star hotels in South-East Coast of North Cyprus to deal with the variable number of visitors by creating a changeable interior architecture and increasing the number of functions through the flexible solutions.

ÖZ: İç mimarlıktaki en önemli süreçlerden biri esnekliktir. Esneklik, dinamik bir sistem içinde iç mimarinin tüm alternatif durumlarının ve kalıplarının gereksinimlerine uyum sağlamayı veya daha bağlantılı ve amaçlanan işlevin gereksinimlerini karşılayan tasarlanmış geometrik şekillerin oluşturulmasını ifade eder.Ek olarak, esnek çözümler değiştirilebilir alanlar yaratılmasınave kullanıcı ihtiyaçlarını karşılamak için gerekli işlevler için alanın bölünmesine katkı sağlayabilmektedir. Tezin temel amacı, beş yıldızlı otel standart odalarının işlevsellik ve konfor düzeyini, kullanıcı ve fonksiyon sayısını artırmak için otel standart odalarında değişken bir mekan oluşturmak için araç olarak kullanılan esneklik hakkında kapsamlı bir fikir oluşturmaktır. Bu amaca ulaşmak için öncelikle mevcut endüstrilerden ve daha önce tamamlanmış makaleler, çoklu tezler gibi araştırmalardan esnek çözümler çıkarım yapılacaktır. Ardından, KKTC'nin otelcilik kuralları ve yönetmelikleri incelenecek ve tezde vaka çalışmasıolarak Kuzey Kıbrıs'ın Güneydoğu kıyısı kentlerinde bulunan beş yıldızlı oteller üzerine çalışılacaktır.Ayrıca, vaka çalışmalarının tasarımı ve analizi için temel olarak KKTC sınıflandırmaları incelenecektir.Bundan sonra, esnek çözümlerin otel odasında uygulanması, kullanıcının gereksinimlerini ve değişen alan ihtiyaçlarını karşılamak için esneklik potansiyelini kanıtlamak için araştırılacaktır. Genel olarak, bu çalışma Kuzey Kıbrıs'ın Güneydoğu kıyısında bulunan beş yıldızlı otellerin, değişken bir iç mimari oluşturarak ve esnek çözümlerle fonksiyon sayısını artırarak, değişken ziyaretçi sayısının üstesinden gelmelerine yardımcı olmayı amaçlamaktadır.
Master of Science in Interior Architecture. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Interior Architecture, 2021. Supervisor: Assoc. Prof. Dr. Zehra Öngül
Keywords: Interior Architecture Department; Hotels--Interior Architecture--Cyprus, North; Hotels--Architecture; Interior Architecture, Flexibility, Flexible solutions, Hotels, Five-star Hotel